Peran Umkm Pengolahan Lele dalam Mendorong Pertumbuhan Ekonomi Nasional: Studi Kasus pada UMKM di Kecamatan Ngadiluwih - Ika Nurfitriani; Muhammad Fahmi Sholihudin (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in supporting national economic growth by creating employment opportunities, increasing community income, and generating product value-added. However, catfish-processing MSMEs continue to face several challenges, including limited access to capital, fluctuations in raw material supply, low levels of innovation, and the underutilization of production technology and digital marketing. This study aims to analyze the role of catfish-processing MSMEs in creating product value-added, improving community welfare, and identifying business development strategies that support national economic growth. This study employed a qualitative approach with a case study design conducted at catfish-processing MSMEs in Ngadiluwih District, Kediri Regency, Indonesia. Ten informants were selected using purposive sampling. Data were collected through in-depth interviews, observations, and documentation and analyzed using the interactive model of Miles, Huberman, and Saldaña, consisting of data condensation, data display, and conclusion drawing and verification. The findings indicate that catfish-processing MSMEs enhance product value-added through product diversification, production process innovation, and improved packaging, thereby increasing product competitiveness and market value. Furthermore, these enterprises contribute to community welfare by generating employment, increasing household income, and strengthening local economic activities. Effective development strategies include strengthening supply chain partnerships, expanding access to financing, modernizing production technology, and implementing digital marketing. These findings demonstrate that strengthening the capacity of catfish-processing MSMEs can enhance business competitiveness while reinforcing their contribution to sustainable national economic growth.